Perspectives of medical students on the implementation of sub-internship rotation in year 5 surgical clerkship: A brief report from a private medical college in Pakistan - Amber Sultan; Nadeem A. Siddiqui; Muhammad Anees; Sadaf Khan; Raziuddin Biyabani; Mohammad Nazim (Journal of Education and Health Promotion)
This study aims to explore the perspectives of medical students on the newly introduced Surgical Sub-internship (SI) rotation in year 5 Surgical Clerkship. This cross-sectional study was conducted at The Aga Khan University Hospital, Karachi, Pakistan from September 2022 to September 2023. A self-designed 5-point Likert scale-based evaluation form was created to explore students’ perspectives regarding their one-week Surgical SI rotation. We included students from the class of 2022 and 2023 who completed the surgical SI rotation. A total of 121 medical students from the class of 2022 (n=73,60%) and 2023 (n=48, 40%) participated in the study with a female-to-male ratio of 53 (44%):68 (56%). Students expressed positive attitudes toward the SI rotation, with 92 (76%) agreeing on the accessibility of medical staff/chief residents, 89 (74%) indicating clarity in goals, 86 (71%) understanding practical issues in clinical settings, 83 (69%) recognizing good learning opportunities for practicing essential skills, and 81 (67%) reporting good opportunities to observe and perform procedures. However, 53 (44%) found the rotation duration inadequate for achieving the desired objectives. Written feedback as narrative comments were also received. The commonly identified areas of improvement included effective communication of rotation objectives, a conducive learning environment, patient volume, standardized teaching, operating room exposure, student assignment to interns, resident involvement in teaching, and awareness of the stakeholders. Medical students provided positive perceptions regarding the surgical SI rotation. However, the identified areas of improvement should be integrated to enhance its overall effectiveness.